2013
DOI: 10.5812/ircmj.8793
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Sequence Analysis of LipL32, a Surface–Exposed Lipoprotein of Pathogenic Leptospira Spp

Abstract: BackgroundLeptospirosis is a worldwide zoonosis caused by pathogenic Leptospira species. A major challenge of this disease is the application of basic research to improve diagnostic methods and related vaccine development. Outer membrane proteins of Leptospira are potential candidates that may be useful as diagnostic or immunogenic factors in treatment and analysis of the disease.ObjectivesTo develop an effective subunit vaccine against prevalent pathogenic Leptospira species, we sequenced and analyzed the Lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Numerous studies confirmed its high specificity and sensitivity, with the capability of detecting as few as 10 organisms in a sample (46,47,49,50,60). Leptospiral DNA has been detected in body where antibody titres may be lower and appear later than in serum (34).…”
Section: Polymerase Chain Reactionmentioning
confidence: 95%
See 2 more Smart Citations
“…Numerous studies confirmed its high specificity and sensitivity, with the capability of detecting as few as 10 organisms in a sample (46,47,49,50,60). Leptospiral DNA has been detected in body where antibody titres may be lower and appear later than in serum (34).…”
Section: Polymerase Chain Reactionmentioning
confidence: 95%
“…These genes are highly conserved among various pathogenic Leptospira species. Therefore, these genes are useful for detection of leptospiral infection and suitable for designing of positive control in PCR assay (46)(47)(48)(49)(50). Although PCR is now widely used for the diagnosis of many diseases, its general value for the rapid diagnosis of leptospirosis has not been evaluated worldwide as it is not yet widely used, particularly in tropical and subtropical countries.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence polymorphisms observed in different strains were silent, suggesting the possibility of an evolutionary pressure to maintain the primary sequence of LipL32 in the pathogen. Serovars isolated from geographically connected areas showed more percentage identity than the sequence from a more distant location [9]. There was nearly 94% sequence similarity observed between the LipL32 sequences of all pathogenic strains studied.…”
Section: The Gene and Proteinmentioning
confidence: 97%
“…Attempts have been made to develop enzymelinked immunosorbent assays (ELISAs) for detecting Leptospira-specific antibodies using recombinant Leptospira outer-membrane proteins (OMPs) as antigens (5,6,7,8). The LipL32 protein, which is found abundantly in pathogenic Leptospira, is one of the most important OMPs expressed during human infection (9,10). The recombinant proteins produced using Escherichia coli serve as a biologically safe source of antigens, as live Leptospira are pathogenic and pose a risk of infection among laboratory personnel.…”
Section: Introductionmentioning
confidence: 99%